Obinutuzumab and miniCHOP for unfit patients with diffuse large B-cell lymphoma. A phase II study by Fondazione Italiana Linfomi. Issue 1 (January 2020) - Merli, Francesco; Cavallo, Federica; Salvi, Flavia; Tucci, Alessandra; Musuraca, Gerardo; Nassi, Luca; Merli, Michele; Tani, Monica; Gini, Guido; Ferrari, Angela; Molinari, Anna Lia; Liberati, Anna Marina; et al.
ABSTRACT: Objective: To evaluate activity and safety of obinutuzumab-miniCHOP (Ga101-miniCHOP) combination in older patients with Diffuse Large B-Cell Lymphoma (DLBCL) unfit to receive full dose immunochemotherapy. Materials and Methods: We conducted a Simon's two-stage phase II multicenter trial to investigate response rate (primary endpoint) and safety of six courses of Ga101-miniCHOP in older patients with DLBCL (≥65 years), prospectively defined as unfit according to a simplified Comprehensive Geriatric Assessment (sCGA). Results: Overall, 34 patients were enrolled (median age 82 years; range 68–89), with 27 out of the 33 eligible patients completing all six planned courses. Complete Remission (CR) rate was reported in fourteen patients (42%). After a median follow-up of sixteen months, the two-year Progression Free and Overall Survival (PFS and OS) were 49% (95% Confidence Interval (CI), 28 to 67) and 68% (95% CI, 49 to 81), respectively. The most frequent grade 3–4 adverse event was neutropenia in thirteen patients (26%). Conclusions: Based on the observed CR rate, study accrual was interrupted due to the very low probability of demonstrating the initial study hypothesis that Ga101-miniCHOP could improve results of historical data obtained with R-miniCHOP in this group of patients. Nonetheless, results achieved with the 33 treated patients confirm activity and good tolerability of the Ga101-miniCHOP regimen for older unfit adult patients with DLBCL.